Symptom trajectories of post-COVID sequelae in patients with acute Delta or Omicron infection in Bergen, Norway - Iversen, Arild; Blomberg, Bjørn; Haug, Kjell; Kittang, Bård; Özgümüs, Türküler; Cox, Rebecca Jane; Langeland, Nina (Frontiers in Public Health, 2024)
Introduction A substantial proportion of the over 700 million COVID-19 cases world-wide experience long-term symptoms. The objectives of this study were to compare symptom trajectories and risk factors for post-COVID-19 condition after Delta and Omicron infection. Methods This study consecutively recruited patients with SARS-CoV-2 infection from November 2021 to March 2022. We recorded demographics, comorbidities, vaccination status, sick leave, and 18 symptoms during acute infection and after 4 months. The primary outcome measures were symptoms during acute infection and after 4 months. Secondary outcome measures were work and school absenteeism. Results We followed a cohort of 1,374 non-hospitalized COVID-19 patients in Bergen, Norway, at three time points. The median age was 39.8 years and 11% were children <16 years. Common acute upper respiratory symptoms waned during follow-up. Fatigue remained common from acute infection (40%) until after 4 months (37%). Four months post-infection, patients reported increased frequencies of dyspnea (from 15% during acute illness to 25% at 4 months, p < 0.001), cognitive symptoms (from 9 to 32%, p < 0.001) and depression (from 1 to 17%, p < 0.001). Patients infected with Omicron reported less dyspnea (22% versus 27%, p = 0.046) and smell/taste problems (5% versus 19%, p < 0.001) at 4 months follow-up than those with Delta infection. Comorbidities and female sex were risk factors for persistent dyspnea and cognitive symptoms. Ten percent reported sick leave after acute illness, and vaccination reduced the risk of absenteeism (adjusted risk ratio: 0.36, 95% confidence interval: 0.15, 0.72, p = 0.008). Conclusion At 4 months, home-isolated patients infected with Omicron reported overall comparable symptom burden, but less dyspnea and smell/taste problems than Delta infected patients. Several acute symptoms waned during follow-up. It is worrying that dyspnea, neurocognitive symptoms, and particularly depression, increased significantly during the first 4 months after acute infection. Previous vaccination was protective against prolonged sick leave.